REVISITING THE WRITTEN SUBJECT-VERB AGREEMENT OF THE ELEVENTH GRADERS ON DESCRIPTIVE TEXT: SURFACE STRATEGY ANALYSIS - Riana Arum Sari; Sri Wahyuni (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Many studies examining the subject-verb agreement errors in students’ writing have been conducted; however, it still needs further exploration to revisit students' success in writing a text. The objectives of this study are analyzing students' errors related to the subject- verb agreement and revisiting the success of students in writing a descriptive text. To achieve those purposes, a total of 36 students from the eleventh class Accounting 5 from SMKN 2 Kediri were asked to write descriptive text on the topic provided. In addition, the researcher also conducted interviews with the teacher and several students. The findings showed that the participants contributed three types of subject-verb agreement errors in their descriptive writing, those were omission (38%), addition (8%) and misformation (54%), then misordering error was not found in this research. It was also revealed that students are also successful in writing descriptive texts in terms of using general structures, language features, tense, and quantifiers in writing descriptive text.